Žemės ūkio padėtis Rytų Lietuvoje vadinamosios „Vidurio Lietuvos" laikotarpiu ir žemės reformos darbų pradžia - Kankevičius, Artūras (Lietuvos istorijos studijos, 1997)
After the end of Lucjan Zeligowsky's „revolt," so-called „Middle Lithuania" government was established, which was ostensibly independent from Warsaw policy. When the military operations were over, the situation inside the country was extremely critical. The economy of Eastern Lithuania, the base of which was agriculture, was completely ruined. New authority in 1921 had started partial reconstruction of the country's agriculture owing to the help of Warsaw. The attempts were made to provide farmers with seeds, necessary equipment, also to gain the pre-war number of cattle in Eastern Lithuania. The lack of land, radical slogans from the East made the question of land structure reform important. The land reform had to stabilize the country's inside situation. In spite of the formal situation in the Middle Lithuania, the decree of General Lucjan Zeligowsky „Concerning the question of land reform" was declared.  The decree, repeating the main principles stated in the Polish laws, was more peasant in its essence. Agrarian councils were established in the Middle Lithuania, the main task of which became the parceling of large landownership. The parcelling of land took place in two directions: the state estates were being parcelled, and alongside this, the parcelling of private large landownership took place under control of Land departments. In 1922, 17,440 dessiantines of land area were distributed in plots. 1009 plots were formed, the buyers of which became the countrymen of the nearest villages. The fact that the owners of the new plots became landless and poor peasants was not less important. The works of dividing villages into individual farms and the liquidation of servitudes were begun. The results gained in this field were poor.  The laws of the Middle Lithuania land reforms had great importance on the further development of agrarian relationships in Eastern Lithuania. This reform was different in its essence not only from the laws of the Republic of Poland but also prevented the establishment of laws devoted to the Kresy.